Разработка интегрированной САПР технологических процессов интенсивного пластического деформирования на примере реверсивного сдвига - Алтухов, Александр Валерьевич; Тарасов, Александр Федорович; Поднебесный, Николай Николаевич; Винников, Артем Олегович (НТУ "ХПИ", 2017)
Выполнен анализ проблем, возникающих при разработке САПР штамповой оснастки для процессов интенсивного пластического деформирования (ИПД). Разработан модуль интегрированной САПР для CAE-системы ABAQUS, позволяющий автоматизировать создание расчетной модели процесса реверсивного сдвига (РС) и его модификаций. Разработанный модуль позволил провести исследования технологического процесса ИПД по схеме РС при изменении ряда технологических параметров.

The problems arising in the development of CAD for tools design for the processes of severe plastic deformation (SPD) was analyzed. The structure of the developed integrated CAD which includes industrial CAD/CAE-systems is considered. The scheme of the tooling and the parameters of the geometric model of the SPD process for the example of the modified reverse shear (RS) are given. The integrated CAD module for the CAE-system ABAQUS has been developed allowing to automate the creation of the design model of the reverse shear (RS) process and its modifications. A feature of modeling in the CAE-system of SPD processes is considered, which can include many calculation steps with spatial displacement and positioning of the workpiece between operations. The developed module made it possible to conduct studies of the technological process of SPD according to the RS scheme with the modification of a number of technological parameters. The analysis of the influence of technological parameters on the unevenness of deformation on the volume of the billet is made.
Development of integrated CAD for technological processes of severe plastic deformation using the example of reverse shear
Keywords: параметрическое проектирование; САЕ-система; штамповая оснастка; реверсивный сдвиг; интенсивное пластическое деформирование; parametric design; die tools